Aztec autumn - Jennings, Gary. (New York : Tor Books, 1998)
A sequel to the novel "Aztec," set in postconquest Mexico, which tells the story of Tenamaxtli, a proud, young Aztec who sets out to avenge the murder of his father by mounting a rebellion against the Spaniards.
"A Tom Doherty Associates book."
Sequel to: Aztec.
Adult.
Adult
Keywords: Aztecs -- Fiction; Indians of Mexico -- Fiction; Aztecs -- Fiction; Historical fiction; Native Americans -- Mexico -- Fiction; Historical fiction